Supply chain integration capability: A three-stage circular model of visibility, agility, and flexibility - Wang, Michael; Wang, Bill; Kim, Namwoon; Chan, Ricky; Wang, Mengmeng; Shi, Yangyan (Journal of general management, 2024)
This paper presents supply chain capabilities in a three-stage circular model. Different from most studies exploring supply chain integration (SCI) from the perspective of processes, this paper studies SCI from a holistic approach. By applying dynamic capability view (DCV), this study develops a measurement of SCI capability based on the three-stage circular model. The scale items were drawn from existing literature. A survey study gathered 187 responses from firms in New Zealand. Factor analysis was conducted to validate the measurement of supply chain integration in the New Zealand businesses. The paper defines the SCI capability as a second-order construct including several well-studied dynamic capabilities such as visibility, agility, and flexibility. The three-stage circular model enables firms to learn, response, and reconfigure to achieve rapid continuous improvement in supply chains. This paper provides new insights and practical implications in SCI and supply chain capability studies and practices in the Industry 4.0 era.